2001
DOI: 10.1128/jcm.39.11.4086-4092.2001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Environmental Isolates of Vibrio cholerae Serogroup O141 Carry the CTX Phage and the Genes Encoding the Toxin-Coregulated Pili

Abstract: We report sporadic cases of a severe gastroenteritis associated with Vibrio cholerae serogroup O141. Like O1 and O139 serogroup strains of V. cholerae isolated from cholera cases, the O141 clinical isolates carry DNA sequences that hybridize to cholera toxin (CT) gene probes. The CT genes of O1 and O139 strains are carried by a filamentous bacteriophage (termed CTX phage) which is known to use toxin-coregulated pili (TCP) as its receptor. In an effort to understand the mechanism of emergence of toxigenic O141 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
115
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 44 publications
5
115
0
Order By: Relevance
“…However, our results contradict the assumption that most cholera toxin-producing strains are also positive for TCP, since TCP is known to be the receptor for CTXφ infection of V. cholerae. In fact, our results appear to be consistent with data from recent studies that report the presence of the two virulence genes found in epidemic strains, ctxAB and tcpA, in environmental and clinical strain of serogroups other than O1 and O139 5,10,27,28,31,32 .…”
Section: Discussionsupporting
confidence: 82%
“…However, our results contradict the assumption that most cholera toxin-producing strains are also positive for TCP, since TCP is known to be the receptor for CTXφ infection of V. cholerae. In fact, our results appear to be consistent with data from recent studies that report the presence of the two virulence genes found in epidemic strains, ctxAB and tcpA, in environmental and clinical strain of serogroups other than O1 and O139 5,10,27,28,31,32 .…”
Section: Discussionsupporting
confidence: 82%
“…Additional analyses demonstrate that the gene encoding VcRtxA is absent in O1 classical biotype strains of V. cholerae because of a 7-kb deletion within the rtx operon (4), but is present in El Tor, O139, and non-O1 clinical and environmental isolates (9)(10)(11). The ubiquitous presence of VcRtxA suggests that this toxin is an important virulence factor of V. cholerae.…”
mentioning
confidence: 99%
“…Most nonpathogenic, environmental isolates express other O antigens and are referred to as ''non-O1, non-O139.'' However, some non-O1, non-O139 V. cholerae are clearly pathogenic and have caused outbreaks or sporadic cases of gastroenteritis and extraintestinal infections in humans (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%